Ailing Philippine health: proof of market failings - Melgar, Junice (1999)
Junice Melgar sees the Philippine health system as a complex product of economic neoliberalism, patronage politics and internal bureaucratic inertia. She examines the ramifications of privatization and globalization on the Philippine drug industry, the outmigration of Philippine health professionals and government health policy responses. - Reproduced
Keywords: Health services - Philipines; Health services